The observation of congenital retroperitoneal large size neuroblastoma - Starchenko, I.I.; Dyachenko, L.V.; Prylutskyi, О.K.; Vynnyk, N.I.; Filenko, B.M. (PH Akademperiodyka, 2023)
Summary. The article represents current literature data on epidemiological, clinical-morphological features and diagnostic criteria of neuroblastoma. The case of large congenital neuroblastoma with multiple metastases in the newborn child is presented. The histological picture and immunohistochemical profile of the tumor allowed us to consider this type of neuroblastoma as the least differentiated variant (subtype, “neuroblastoma rich in Schwann stroma”), with rapid progression and metastasizing started before the birth of the child.